Searching for Expressiveness, Modularity, Flexibility and Standardisation in Software Process Modeling - Ribó, Josep M.; Franch, Xavier (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de Software, 2000)
Although an important research effort has been carried out in the last decade in the field of software process modelling (SPM), some crucial issues still remain as challenges to the community. The expressive power of process control-flow descriptions in most current approaches is still not optimal: their capabilities to provide a flexible process model in which it is possible to perform "on-the-fly" modifications in a safe manner are often insufficient and, usually, their modularity features are limited. Furthermore, the research community has not succeeded in finding a standard process modelling language, which has clearly impaired the development of the area. In this article we propose some objectives to be accomplished concerning the above-mentioned aspects and we provide an overview of some different approaches to these issues that have been already developed. We compare tem and we stress both their strong points and their limitations. As part of this analysis, we outline the PROMENADE approach to software process modelling, aimed at solving these limitations while keeping the strong points by means of the use of a complete set of control-flow and modularity constructs. To enhance standardisation, PROMENADE constructs are defined in terms of UML: UML constructs support also specialisation and flexibility of process models.